2018
DOI: 10.1186/s12891-018-1969-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adolescent physical activity-related injuries in sports, leisure time, and school: the National Physical Activity Behaviour Study for children and Adolescents

Abstract: BackgroundThe purpose of this study was to investigate the prevalence of adolescent physical activity-related injuries in sports club activities, leisure time physical activity and school-based physical activity. The secondary aim was to investigate the differences in the prevalence of physical activity -related injuries between years 2014 and 2016. In addition, we set out to study the associations between age, sex and the frequency of physical activity and injury prevalence.MethodsThis cross-sectional study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 39 publications
2
21
3
Order By: Relevance
“…Supervisors' presence around children can help to enforce safe behavior and allow for timely intervention in case of aggressiveness and intentionally inflicted injuries among students. Contrary to existing literature, our study reported a low rate of sports-related injuries compared to unstructured play activities [41][42][43]. This may be explained by a relatively limited organized sports activity at schools in Lebanon, related to their associated setting and facility costs.…”
Section: Frequency (%)contrasting
confidence: 98%
“…Supervisors' presence around children can help to enforce safe behavior and allow for timely intervention in case of aggressiveness and intentionally inflicted injuries among students. Contrary to existing literature, our study reported a low rate of sports-related injuries compared to unstructured play activities [41][42][43]. This may be explained by a relatively limited organized sports activity at schools in Lebanon, related to their associated setting and facility costs.…”
Section: Frequency (%)contrasting
confidence: 98%
“…Examination of the SDQ scores (Table 1) shows higher scores for boys, and prevalence of pain is elevated in children with ADHD, which is predominant in boys [37]. In addition, behaviour may also explain the sex difference reported in this study: although both girls and boys report similar individual sport participation (73%), boys participated in team sport more often than girls (girls = 54%, boys = 74%) and boys are more likely to sustain musculoskeletal injury from sport participation both as individuals and within team sports [38,39]. Sleep problems may also have a role in promoting the persistence or worsening of musculoskeletal pain [32].…”
Section: Discussionmentioning
confidence: 70%
“…There is some risk of injuries or overuse injuries among children and adolescents who participate in physical activities and sports, 123 as well as organised and unorganised leisure-time physical activity, 1 2 with the evidence suggesting high numbers of injuries when participating in sports-related activities, 124 unorganised activities 125 and high-risk sports (eg, ice hockey). 126 In general, as the level of physical activity increases, the likelihood of injury increases.…”
Section: Statementsmentioning
confidence: 99%